Etika Pelayanan Publik Di Kantor Lurah Mangalli Kecamatan Pallangga Kabupaten Gowa - Perdana, Muh Rian; Razak, Andi Rosdianti; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This research is to find out the Ethics of Public Service in the Mangalli Village Office, Pallangga District, Gowa Regency. This study uses a type of qualitative research using data collection techniques through in-depth interviews (in-depth interviews). The results of the study show that service ethics based on rights agreements have been going well because they have served the community regardless of race, ethnicity, religion and politics. The service ethic, namely justice here, has been well implemented by serving the community in a friendly manner. Furthermore, loyalty in the form of special honorary employees remains loyal to the agency regardless of how much salary they receive. And for accountability, it has not been fully implemented properly where employees arrive late to the office and go home before the set hour and employees who are still on an honorary status do not come to the office every day, so the service does not go well.